ANALISIS PENGARUH STRES KERJA DAN LINGKUNGAN KERJA NON FISIK TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan Departemen Spinning PT. Daya Manunggal Salatiga) - Prasasti, Vivin Tri; Yuniawan, Ahyar (Diponegoro Journal of Management, 2017)
This study aims to analyze the effect of job stress, and non physical work environment to organizational citizenship behavior with organizational commitment as intervening variable. The strict competition between companies nowadays evokes some effects to the employees, one of them is job stress. High job stress level can decrease their organizational commitment that leads to the declining of organizational citizenship behavior which affected directly by organizational commitment. This study was done on spinning department at PT. Daya Manunggal in Salatiga. The sample used 100 respondents using simple random sampling method. Likert scale is used to measure the questionnaire. The data analysed using SPSS ver. 20. Sobel test used to test the mediation effect. The results from the analysis show that job stress affects significantly negative to organizational citizenship behavior, and non-physical work environment affects significantly positive to organizational citizenship behavior. Another result of this study also shows that organizational commitment is a strong antecedent towards organizational citizenship behavior and is an excellent between job stress and non-physical work environment towards organizational citizenship behavior.